Luminescence and Stability Enhancement of CsPbBr3 Perovskite Quantum Dots through Surface Sacrificial Coating. Issue 16 (18th May 2021) - Huang, Dong; Bo, Jun; Zheng, Ronghong; Luo, Chengzhao; Sun, Xiaojuan; Li, Qinyi; Shen, Dongyang; Zheng, Zhishuai; Chen, Mengyu; Yang, Yixing; Tang, Aiwei; Chen, Song; et al.
Abstract: All‐inorganic perovskite quantum dots (QDs) have emerged as a new category of low‐cost semiconducting luminescent materials for optoelectronic applications. However, their poor stability has become the main challenge that impedes their potential applications. Herein, Ni‐doped CsPbBr3 QDs with lead phosphate (Pb3 (PO4 )2 ) shell through surface sacrificial coating (c‐Ni‐CsPbBr3 ) have been developed based on a modified thermal injection approach. The synergistic effect of Ni doping and Pb3 (PO4 )2 coating effectively improves the stability and optical performances of CsPbBr3 QDs, including photoluminescence (PL) intensity, the average lifetime, and PL quantum yield (QY). Thus, the c‐Ni‐CsPbBr3 QDs demonstrate the full width at half maxima (FWHM) and PLQY being 18.42 nm and 90.77%, respectively. The PL intensity of c‐Ni‐CsPbBr3 can be maintained at 81% of its original value after being heated at 100 °C for 1 h. No phase transformation can be observed after being stored under ambient conditions (25 °C, 60% relative humidity (RH)) for 21 days. In addition, by combining green c‐Ni‐CsPbBr3 QDs, red CdSe‐based QDs and the blue GaN chip, a QD enhancement film (QDEF) is fabricated to form a liquid crystal display (LCD) backlit with a wide color gamut covering cover 121% of the National Television System Committee (NTSC) standard. Abstract : The synergistic effect of Ni‐doping and lead phosphate coating passivates the structural and surface defects of CsPbBr3 quantum dots (QDs), thereby enhancing their optical performance and stability in air, heat, water, and humid environment. A QD enhancement film is fabricated to form a liquid crystal display backlit with a wide color gamut covering 121% of the National Television System Committee standard.